2016
DOI: 10.1007/s10940-016-9287-8
|View full text |Cite
|
Sign up to set email alerts
|

Educational Outcomes After Serving with Electronic Monitoring: Results from a Natural Experiment

Abstract: Objectives The paper explores the effects of electronic monitoring (EM) on young offenders' educational outcomes and contributes to the evaluation of EM as a non-custodial sanction with a new outcome measure. MethodsThe study is based on a natural experiment exploiting a reform in Denmark in 2006 introducing electronic monitoring to all offenders under the age of 25 with a maximum prison sentence of 3 months. Information on program participation is used to estimate instrument variable models in order to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
1
11
0
2
Order By: Relevance
“…Existing research has shown that, compared to imprisonment, electronic monitoring decreases criminal recidivism (e.g., Di Tella & Schargrodsky, ), strengthens the labor market, and improves the educational outcomes of offenders (e.g., Andersen & Andersen, ; Larsen, ). Also, at least in Denmark, electronic monitoring is cheaper to run than imprisonment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research has shown that, compared to imprisonment, electronic monitoring decreases criminal recidivism (e.g., Di Tella & Schargrodsky, ), strengthens the labor market, and improves the educational outcomes of offenders (e.g., Andersen & Andersen, ; Larsen, ). Also, at least in Denmark, electronic monitoring is cheaper to run than imprisonment.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has studied how alternatives to imprisonment affect, for example, criminal recidivism (e.g., Di Tella & Schargrodsky, ), labor market attachment (e.g., Andersen & Andersen, ), educational achievement (Larsen, ), and children's foster care placements (Andersen & Wildeman, ). Our study is the first to isolate the effect of a noncustodial alternative to imprisonment, such as electronic monitoring, on relationship dissolution and on singlehood.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of EM in Denmark also offers quasi-experimental evidence from Europe, but existing studies focus on the effect of EM on social welfare dependence (Andersen and Andersen, 2014) or educational outcomes (Larsen, 2016), not future criminal activity.…”
Section: Related Literaturementioning
confidence: 99%
“…Andersen and Andersen (2014) found that being assigned to EM reduced days spent on welfare, but only for young offenders (age 25 or under). Larsen (2017) found that EM, which was paired with a work or education requirement, increased young offenders' secondary school completion. Neither study considered effects on recidivism, but both suggest that EM facilitates successful reintegration for young, low-level offenders, when used as an alternative to short incarceration spells.…”
Section: Electronic Monitoringmentioning
confidence: 97%